Quality-Adjusted Life Years After Hip and Knee Arthroplasty: Health-Related Quality of Life After 12, 782 Joint Replacements. Issue 3 (25th September 2018) - Konopka, Joseph F.; Lee, Yuo-yu; Su, Edwin P.; McLawhorn, Alexander S.
Abstract : Background: The quality-adjusted life year (QALY) is the preferred outcome measurement for cost-effectiveness analysis in health care. QALYs measure patient health-related quality of life with use of a value between 0 and 1. Few studies have provided original data delineating QALYs after hip and knee arthroplasty. In the present study, we evaluated patient utility preoperatively and 2 years after total hip arthroplasty, hip resurfacing, revision hip arthroplasty, total knee arthroplasty, unicompartmental knee arthroplasty, and revision knee arthroplasty. Methods: A single-hospital joint registry, which enrolled patients from 2007 to 2011, was retrospectively examined for all patients who underwent primary or revision hip or knee arthroplasty and who had preoperative and 2-year postoperative Short Form-36 (SF-36), Short Form-12 (SF-12), or EuroQol 5-Dimension (EQ-5D) scores available. Patient age, body mass index (BMI), sex, American Society of Anesthesiologists (ASA) score, and Charlson Comorbidity Index were recorded. QALYs were determined from the EQ-5D index and the Short Form-6 Dimension (SF-6D) index. Results: Five thousand, four hundred and sixty-three patients underwent total hip arthroplasty, with a mean annual increase (and standard deviation) of 0.25 ± 0.2 QALY; 843 patients underwent hip resurfacing, with a mean annual increase of 0.24 ± 0.17 QALY; 5, 398 patients underwent primary total knee arthroplasty, with a mean annual increase of 0.17 ± 0.19 QALY; and 240 patients underwent medial unicompartmental knee arthroplasty, with a mean annual increase of 0.16 ± 0.17 QALY. Aseptic revision arthroplasty (440 hips, 323 knees) was associated with a smaller QALY gain than primary arthroplasty. Patient age, BMI, female sex, ASA category, and higher preoperative health-related quality of life were negative predictors for QALY gain after primary arthroplasty. Forty additional hip procedures and 35 additional knee procedures were also analyzed. Conclusions: Primary hip and knee arthroplasty, on average, result in substantially increased patient quality of life. Revision hip and knee replacement result in a lower, but still positive, gain in quality of life. However, there is a considerable variation in patient outcomes across all procedures. Our results may be used to improve the certainty of future cost-effectiveness analyses of hip and knee arthroplasty. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.